2018
DOI: 10.1519/jsc.0000000000002373
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effect of Citrulline Malate Supplementation on Upper-Body Resistance Exercise Performance in Recreationally Resistance-Trained Men

Abstract: To investigate the effect of citrulline malate (CM) supplementation on upper-body resistance exercise performance, twelve recreationally resistance-trained men (21.4±1.6 y; 163.0±46.2 cm; 85.0±12.4 kg) underwent two testing sessions administered in a randomized, double-blind fashion. During each visit, participants were provided either 8 g of CM or a placebo (PL) 40 min prior to beginning a standardized warm-up and initiating a barbell bench press resistance exercise protocol consisting of 5 sets of 15 repetit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 19 publications
4
31
1
Order By: Relevance
“…The present investigation has also not demonstrated the effects of CIT supplementation on muscle resistance (maximum repetitions), as well as on PSE. These results corroborate previous studies 36,37 that did not identify ergogenic benefits in muscle resistance. In line with the present study, Cutrufello et al 13 examined the ingestion effects of a single dose of L-citrulline (6 g) or 710 ml of watermelon juice (approximately 1 g of citrulline) on the number of repetitions achieved in the bench press exercise, time to exhaustion, maximum oxygen consumption and anaerobic threshold during a maximum treadmill test.…”
Section: Bendahan D Matteisupporting
confidence: 92%
“…The present investigation has also not demonstrated the effects of CIT supplementation on muscle resistance (maximum repetitions), as well as on PSE. These results corroborate previous studies 36,37 that did not identify ergogenic benefits in muscle resistance. In line with the present study, Cutrufello et al 13 examined the ingestion effects of a single dose of L-citrulline (6 g) or 710 ml of watermelon juice (approximately 1 g of citrulline) on the number of repetitions achieved in the bench press exercise, time to exhaustion, maximum oxygen consumption and anaerobic threshold during a maximum treadmill test.…”
Section: Bendahan D Matteisupporting
confidence: 92%
“…However, not all studies have observed ergogenic effects of citrulline malate consumption. Two recent studies failed to show improvement in performance, augment the muscle swelling response to training, alleviate fatigue or increase focus and energy following citrulline malate supplement in recreational resistance trained men [112,113].…”
Section: Dietary Supplementsmentioning
confidence: 99%
“…Nevertheless, several studies have investigated the ergogenic potential of CitMal supplementation on both aerobic and anaerobic exercise performance (Gonzalez & Trexler, 2020). Due to its potential to delay fatigue during highintensity exercise, studies have specifically investigated the acute effects of CitMal supplementation on strength, power, and resistance training performance (Chappell et al, 2018a(Chappell et al, , 2018bCunniffe et al, 2016;Cutrufello et al, 2015;da Silva et al, 2017;Farney et al, 2017;Glenn et al, 2015Glenn et al, , 2016Gonzalez et al, 2017;Martínez-Sánchez et al, 2017;Pérez-Guisado & Jakeman, 2010;Trexler et al, 2019a;Wax et al, 2015aWax et al, , 2015b. Although these studies have offered mixed findings, some have shown that acute CitMal supplementation may increase performance during highintensity strength and power tasks.…”
mentioning
confidence: 99%
“…Here, several of the studies have demonstrated that subjects who consume a single dose of CitMal (6-8 g) experience less fatigue to the working muscles compared with a placebo groupallowing them to perform more repetitions to failure (Pérez-Guisado & Jakeman, 2010;Wax et al, 2015aWax et al, , 2015b). However, not all studies have shown such favorable results (Chappell et al, 2018a(Chappell et al, , 2018bda Silva et al, 2017;Gonzalez et al, 2017). Recently, a published meta-analysis has indicated a small beneficial effect of CitMal supplementation on high-intensity strength and power performance; however, the analysis included several different strength and power variables from resistance training and sprinting performance tests involving large muscle groups (Trexler et al, 2019b).…”
mentioning
confidence: 99%